Students’ Perceptions Toward The Use of ChatGPT in Improving Writing Skills - Hastri Firharmawan; Nur Anifa (Jurnal Educatio FKIP UNMA, 2026)
The integration of Artificial Intelligence (AI) in education has significantly influenced language learning, particularly in writing instruction. One of the most widely used AI tools is ChatGPT, which offers various features that can support students in developing their writing skills. This study aimed to explore students’ perceptions toward the use of ChatGPT in improving writing skills. The study employed a mixed-method sequential explanatory design. Quantitative data were collected through questionnaires distributed to 30 second-semester students of the English Education Study Program at UMNU Kebumen, while qualitative data were obtained through semi-structured interviews with five selected participants. The findings revealed that students generally had positive perceptions toward the use of ChatGPT. Among the four indicators, Perceived Usefulness obtained the highest mean score (3.94), followed by Perceived Benefits (3.78) and Perceived Ease of Use (3.63). Meanwhile, Concerns and Anxieties showed a moderate level (3.42), indicating that students still had concerns regarding dependency, plagiarism, and information accuracy. The qualitative findings further showed that students viewed ChatGPT as a helpful tool for generating ideas, improving grammar, enriching vocabulary, and increasing writing confidence. However, students also emphasized the importance of using ChatGPT critically and responsibly. Overall, this study concludes that ChatGPT has strong potential to support EFL students’ writing development when used appropriately as a supporting learning tool.